The Great Columbia Plain : A Historical Geography, 1805-1910 - Meinig, D. W. (Donald William), 1924-2020 (Book collections on Project MUSE., 1995)
Dismissed in early years as a wasteland, the rolling open country that covers the interior parts of Washington, Oregon, and Idaho is today one of the richest farmlands in the nation. This work is the story of its transformation. Meinig traces all of the aspects of its development by combining geographic description with historical narrative.